Curating Organizational Memory The Art of Forgetting in the Information Age. - Gilman-Sevčík, Tim (Cambridge Scholars Publishing, 2022)
Why does technology obsessively seek to artificially enhance and expand our memory? We don't have to accept information overload and interconnectedness as the backbones of our age. Our most trusted organizations, schools, and businesses are increasingly burdened by institutionalized storage and an accumulation of knowledge capital. As this book shows, by incorporating forgetting into their strategies for change, they can evolve within this time of radical adaptation.Our fear of forgetting may be blocking a real understanding of how innovative thought forms in our mediated capitalism. Anti-inst.